2023
DOI: 10.1002/dro2.42
|View full text |Cite
|
Sign up to set email alerts
|

Tuning static drop friction

Abstract: The friction force opposing the onset of motion of a drop on a solid surface is typically considered to be a material property for a fixed drop volume on a given surface. However, here we show that even for a fixed drop volume, the static friction force can be tuned by over 30% by preshaping the drop. The static friction usually exceeds the kinetic friction that the drop experiences when moving in a steady state.Both forces converge when the drop is prestretched in the direction of motion or when the drop show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There are many methods to study drop dynamics, such as using de-/inflated drops 9 , magnetically controlled oscillated drops 10 , direct force measurements with force sensors 11 , 12 , and sliding drops on a tilted surface 13 . When drops slide down tilted surfaces, the external gravitational force driving the motion, , can be adjusted by the tilt angle , to control droplet velocity in a wide range.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods to study drop dynamics, such as using de-/inflated drops 9 , magnetically controlled oscillated drops 10 , direct force measurements with force sensors 11 , 12 , and sliding drops on a tilted surface 13 . When drops slide down tilted surfaces, the external gravitational force driving the motion, , can be adjusted by the tilt angle , to control droplet velocity in a wide range.…”
Section: Introductionmentioning
confidence: 99%
“…The design principles presented here provide a foundation for new types of surfaces relevant to superwater repellent applications, [ 39 ] liquid encapsulation, [ 33,40 ] and microreactors, [ 41,42 ] and may also have an application to strain controllable liquid–liquid separations [ 43 ] or droplet catch‐and‐release. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…4c) 90 . Recently, Laroche et al showed that static F fric can vary by as much as 30% depending on how the drop is deposited, whereas kinetic F fric is independent of drop history 91 .…”
Section: Wetting Force Measurementsmentioning
confidence: 99%